George Whitefield: life, context, and legacy - Hammond, Geordan; Jones, David Ceri (Oxford University Press, 2016)
George Whitefield (1714-70) was one of the best known and most widely travelled evangelical revivalist in the eighteenth century. This collection offers a major reassessment of Whitefield's life, context, and legacy, bringing together a distinguished interdisciplinary team of scholars from both sides of the Atlantic. In chapters that cover historical, theological, and literary themes, many addressed for the first time, the volume suggests that Whitefield was a highly complex figure who has been much misunderstood